Topics in Business Finance and Accounting (Book Review). - Zeff, Stephen A.; Stevenson, Harold W. (The Accounting Review, 1965)
Reviews the book "Topics in Business Finance and Accounting," by J.W. Bennett, J. McB. Grant and R.H. Parker.